A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka - Wickramasinghe, L. J. Mendis; Vidanapathirana, Dulan Ranga; Kandambi, H. K. Dushantha; Pyron, R. Alexander; Wickramasinghe, Nethu (Zootaxa, 2017)
We describe a new species, Aspidura ravanai sp. nov., representing the eighth species of the genus known from Sri Lanka. The new species is readily distinguished from all other congeners by its colour pattern, scalation, and genetic distinctiveness. Our molecular results indicated that Aspidura began diversifying in the Miocene approximately 18 Ma, and A. ravanai sp. nov. diverged from its likely sister lineage A. trachyprocta at least 6.2 Ma. The species is currently known only from the type locality, on the western slopes of Sri Pada Peak in the central highlands of Sri Lanka.